Simple Fast Quantification of Cholecalciferol, 25-Hydroxyvitamin D and 1,25-Dihydroxyvitamin D in Adipose Tissue Using LC-HRMS/MS - Bonnet, Laurianne (Nutrients, 2019)
Vitamin D metabolism is actively modulated in adipose tissue during obesity. To better investigate this process, we develop a specific LC-HRMS/MS method that can simultaneously quantify three vitamin D metabolites, i.e., cholecalciferol, 25-hydroxyvitamin D(3) (25(OH)D(3)), and 1,25-dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) in a complex matrix, such as mouse adipose tissue and plasma. The method uses pretreatment with liquid–liquid or solid–phase extraction followed by derivatization using Amplifex(®) reagents to improve metabolite stability and ionization efficiency. Here, the method is optimized by co-eluting stable isotope-labelled internal standards to calibrate each analogue and to spike biological samples. Intra-day and inter-day relative standard deviations were 0.8–6.0% and 2.0–14.4%, respectively for the three derivatized metabolites. The limits of quantification (LoQ) achieved with Amplifex(®) derivatization were 0.02 ng/mL, 0.19 ng/mL, and 0.78 ng/mL for 1,25(OH)(2)D(3), 25(OH)D(3) and cholecalciferol, respectively. Now, for the first time, 1,25(OH)(2)D(3) can be co-quantified with cholecalciferol and 25(OH)D(3) in mouse adipose tissue. This validated method is successfully applied to study the impact of obesity on vitamin D status in mice.